Nasopharyngeal microbiome composition by SARS-CoV-2 presence and severity - Juana Claus; Janetta Top; Fernanda L. Paganelli; Thijs ten Doesschate; Nienke Paternotte; Myka J. Youngapelian; Rob Schuurman; Rob J. L. Willems; Helen Leavis; Janneke H. H. M. van de Wijgert (Scientific Reports)
Abstract The influence of SARS-CoV-2 on the nasopharyngeal microbiome, or vice-versa, is unclear. Nasopharyngeal swabs from Dutch healthcare workers (N = 257) and hospital outpatients with respiratory symptoms (N = 143), leftover after SARS-CoV-2 testing in 2020–2021, were 16S rRNA amplicon sequenced and tested for respiratory viruses by multiplex PCR panel. The healthcare workers were younger and much healthier than the patients, and experienced less severe viral infections. In the healthcare workers, log10 estimated concentrations (ECs) of Corynebacterium were slightly increased in samples with SARS-CoV-2 versus no virus detected, regardless of symptomatology (adjusted regression coefficient 0.52, p = 0.042) but no other bacterial ECs differed. Corynebacterium and Dolosigranulum ECs were higher in very mild/asymptomatic SARS-CoV-2 episodes compared to very mild/asymptomatic episodes with no viruses detected, but lower in mild compared to very mild/asymptomatic SARS-CoV-2 episodes (−1.07, p = 0.015, and −1.37, p = 0.011, respectively). In the patients, similar but non-significant trends by SARS-CoV-2 severity (fatal, severe, moderate versus mild) were seen for Dolosigranulum, but not for Corynebacterium. In this population, the largest nasopharyngeal microbiome composition differences were seen by the presence and severity of comorbidities. These findings suggest that the Dolosigranulum EC decreases with increasing SARS-CoV-2 severity, but the clinical relevance of this finding is unclear.